Analisis Putusan Pengadilan Tata Usaha Negara Tentang Pengangkatan dan Pemberhentian Perangkat Desa dalam Perspektif Siyasah Qadhiyyah (Studi Putusan Perkara Nomor 37/G/2021/Ptun.Mtr) - Ybafih Tanjung, Lara; Hidayat, Rahmat (Dinasti Research, 2024)
The aim of this research is to analyze cases of village officials who were dismissed by the village head. This case occurred in Barejulat Village, Central Lombok Regency, West Nusa Tenggara Province, which stated that the defendant, as village head, dismissed his village officials unilaterally without following Minister of Home Affairs regulation number 67 of 2017. According to the judge's consideration at the State Administrative Court Number 37/G/ 2021/Ptun.Mtr that the object of the dispute, namely the village head's decision, was declared null and void due to procedural defects and ordered the village head to revoke the dismissal decree and reinstate the plaintiff's position. This research is a qualitative method research using a normative legal approach. The source of data collected by this researcher is based on Law Number 6 of 2014 concerning Villages and the Decision of the State Administrative Court Number 37/G/2021/PTUN.MTR.